Non-revascularized chronic total occlusions impact on substrate and post-ablation results in drug-refractory electrical storm - Cojocaru, Cosmin; Nastasa, Alexandrina; Bogdan, Stefan; Iorgulescu, Corneliu; Deaconu, Alexandru; Onciul, Sebastian; Vatasescu, Radu (Frontiers in Cardiovascular Medicine, 2023)
Background and aims There is limited data concerning the effect of non-revascularized chronic total occlusions (NR-CTOs) after VT ablation. This study sought to evaluate the impact of NR-CTOs after ablation for electrical storm (ES). Methods Post-hoc retrospective analysis of data regarding 64 consecutive post-myocardial infarction patients (out of which 12 patients with NR-CTOs and 52 without NR-CTOs) undergoing substrate ablation for ES with an available median follow-up of 37.53 (7.25–64.65) months. Ablation result was assessed by inducibility of sustained monomorphic VT (SMVT) during final programmed ventricular stimulation (PVS). The primary endpoints were all-cause mortality and VT/VF recurrences after ablation, respectively, stratified by the presence of NR-CTOs. The secondary endpoint was to assess the predictive effect of NR-CTOs on all-cause mortality and VT/VF recurrences in relation to other relevant prognostic factors. Results At baseline, the presence of NR-CTOs was associated with higher bipolar BZ-to-total scar ratio (72.4% ± 17.9% vs. 52% ± 37.7%, p = 0.022) and more failure to eliminate the clinical VT (25% (3) vs. 0% (0), p < 0.001). During follow-up, overall all-cause mortality and recurrences were more frequent in the NR-CTO subgroup (75% (9) vs. 19.2% (10), log rank p = 0.003 and 58.3% vs. 23.1% (12), log rank p = 0.042 respectively). After adjusting for end-procedural residual SMVT inducibility, NR-CTOs predicted death during follow-up (HR 3.380, p = 0.009) however not recurrence (HR 1.986, p = 0.154). Conclusions NR-CTO patients treated by RFCA for drug-refractory ES demonstrated a higher ratio of BZ-to-total-scar area. In this analysis, NR-CTO was associated with worse acute procedural results and may as well impact long-term outcomes which should be further assessed in larger patient populations.